2013
DOI: 10.3109/09638288.2013.825332
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in multiple sclerosis patients with bladder, bowel and sexual dysfunction

Abstract: Bladder and sexual dysfunction are associated with a poor health-related quality of life in MS patients. Sexual dysfunction may explain mental health issues among individuals with a short disease duration. Recognition and treatment may prevent the development of more severe sexual and bladder dysfunction and increase physical health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
26
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 31 publications
(77 reference statements)
8
26
0
3
Order By: Relevance
“…In studies conducted by Qaderi (2014) and Tepavccvic (2008), a negative and significant relationship was observed between most dimensions of MSQOL (such as physical health, role limitation due to physical problems, social function and cognitive function) and SD [13,47]. In the present study, a significant difference was found between the women with and without SD in terms of the physical and mental health composites, which agrees with the results obtained by Schairer (2014) and Vitkova (2014), which suggested a negative and significant relationship between SD and the physical and mental dimensions of MSQOL [48,49].…”
Section: Discussionsupporting
confidence: 91%
“…In studies conducted by Qaderi (2014) and Tepavccvic (2008), a negative and significant relationship was observed between most dimensions of MSQOL (such as physical health, role limitation due to physical problems, social function and cognitive function) and SD [13,47]. In the present study, a significant difference was found between the women with and without SD in terms of the physical and mental health composites, which agrees with the results obtained by Schairer (2014) and Vitkova (2014), which suggested a negative and significant relationship between SD and the physical and mental dimensions of MSQOL [48,49].…”
Section: Discussionsupporting
confidence: 91%
“…We read with great interest the work by Vitkova et al [1] dealing with the impact of bladder, bowel and sexual dysfunction (SD) on health-related quality of life (HrQoL) in individuals with multiple sclerosis (MS). Indeed, the authors in their valuable work showed that bladder and SD are associated with a poorer HrQoL, even when the patients have had MS for a relatively short time.…”
mentioning
confidence: 99%
“…2,3 Motor and cognitive impairment, fatigue, depression, pain, incontinence, sexual dysfunction, and the unpredictability of the disease reduce health-related quality of life [4][5][6][7][8][9][10][11] and participation in work and life. 2,12,13 Although it has been difficult to show the effect of multidisciplinary rehabilitation stays in clinical trials, 14,15 several studies have suggested a positive effect of multidisciplinary rehabilitation on disability [15][16][17][18][19][20][21] and aspects of health-related quality of life.…”
mentioning
confidence: 99%